2013
DOI: 10.12740/pp/18147
|View full text |Cite
|
Sign up to set email alerts
|

The importance of hope in coping with schizophrenia

Abstract: Hope is an important dimension of psychological functioning, the source of strength in existential challenges both in health and illness. It is already known that hope is connected with the subjective well-being in people suffering from schizophrenia. Therefore, increasing hope is a promising goal of therapeutic interventions. On the other hand, multiple definitions of hope and methodological differences in the approach to the subject do not lead to determining therapeutic indications, useful in clinical pract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Hope is described as the individual ability in obtaining ideas and driving oneself to achieve the goals (Snyder, 2002). Hope is also found to be a protective factor of attempted suicide among psychotic patients (Libman-Sokolowska & Nasierowski, 2013) and has a positive correlation with functional recovery (Coşkun & Altun, 2017). However, previous studies reported that people with schizophrenia showed a lower level of hope when compared to a healthy population (Coşkun & Altun, 2017;Hayes, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Hope is described as the individual ability in obtaining ideas and driving oneself to achieve the goals (Snyder, 2002). Hope is also found to be a protective factor of attempted suicide among psychotic patients (Libman-Sokolowska & Nasierowski, 2013) and has a positive correlation with functional recovery (Coşkun & Altun, 2017). However, previous studies reported that people with schizophrenia showed a lower level of hope when compared to a healthy population (Coşkun & Altun, 2017;Hayes, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Hope is one of the dimensions of human mental functioning and constitutes an element that integrates human mental life, gives strength in existential struggles in both health and illness. It plays a significant role in activities aimed at improving the broadly understood social functioning of the patient [17].…”
Section: Consequences Of Psychiatric Diagnosismentioning
confidence: 99%